Effector proteins of Funneliformis mosseae BR221: unravelling plant-fungal interactions through reference-based transcriptome analysis, in vitro validation, and protein‒protein docking studies - Pratima Vasistha; Pushplata Prasad Singh; Divya Srivastava; Leena Johny; Sadhana Shukla (BMC Genomics)
Abstract Background Arbuscular mycorrhizal (AM) fungi form a highly adaptable and versatile group of fungi found in natural and man-managed ecosystems. Effector secreted by AM fungi influence symbiotic relationship by modifying host cells, suppressing host defense and promoting infection to derive nutrients from the host. Here, we conducted a reference-based transcriptome sequencing of Funneliformis mosseae BR221 to enhance understanding on the molecular machinery involved in the establishment of interaction between host and AM fungi. Results A total of 163 effector proteins were identified in F. mosseae isolate BR221, of these, 79.14% are extracellular effectors and 5.5% are predicted cytoplasmic effectors. In silico prediction using a pathogen-host interaction database suggested four of the 163 effectors could be crucial in establishing AM fungi-host interactions. Protein–protein docking analysis revealed interactions between these potential effectors and plant proteins known to be differentially expressed during mycorrhizal association, such as defensins, aquaporins, and PTO proteins. These interactions are multifaceted in modulating host physiological and defense mechanisms, including immune suppression, hydration, nutrient uptake, and oxidative stress modulation. Conclusions These findings of the current study provide a foundational understanding of fungal-host molecular interactions and open avenues for exploring pathways influenced by these effectors. By deepening our knowledge of these mechanisms, the use of AM fungi in biofertilizer formulations can be refined by selecting strains with specific effectors that enhance nutrient uptake, improve drought and disease resistance, and tailor the fungi’s symbiotic efficiency to different crops or environmental conditions, thus contributing to more targeted and sustainable agricultural practices.